(untitled) (Proceedings of the World Conference on Waste Management, 2019)
C&D waste management is an area where attention needs to be paid for as the construction industry is considered to be one of the key solid waste generators. Mainly, C&D waste get generated through the new construction, renovation of buildings, and through the demolition of buildings and structures. Hence, it is necessary to manage the C&D waste. In order to manage the C&D waste, it is necessary to identify the types and origins of waste. Thus, the aim of the paper is to identify the types of C&D waste and their origins of generation. This paper critically reviews secondary data and findings of eight case studies under the qualitative approach. Through the case study findings, it was evident that plywood, concrete, cement, steel offcuts, blocks bricks, sand, soil, wood, polythene and food waste as the main types of C&D waste in Sri Lankan construction sites. Further, design changes, transport, human mistakes, quality of works, client changes and mismatches in required materials are identified as the key origins for C&D waste generation in Sri Lankan construction sites. Therefore, to achieve the aim of the paper, types of C&D waste materials and origins of C&D waste generation were identified.